Carotenoids, Fatty Acids, and Volatile Compounds in Apricot Cultivars from Romania-A Chemometric Approach - Adela Pintea; Francisc Vasile Dulf; Andrea Bunea; Sonia Ancuța Socaci; Elena Andreea Pop; Vlăduț-Alexandru Opriță; Daniele Giuffrida; Francesco Cacciola; Giovanni Bartolomeo; Luigi Mondello (MDPI AG, 2020)
Lipophilic constituents are important for the color and aroma of apricots, but also for their health benefits. In the present study, carotenoids, fatty acids, and volatiles were analyzed in 11 apricot cultivars, from which nine were obtained in Romania. High performance liquid chromatography coupled to a diode array detector with atmospheric pressure chemical ionization and mass spectrometry (HPLC-DAD-APCI-MS methodology applied on unsaponified carotenoid extracts allowed the identification and quantification of 19 compounds. The predominant carotenoids in all cultivars were all-trans-β-carotene and its cis isomers. Lutein was present exclusively in non-esterified form, while β-cryptoxanthin was predominantly esterified, mainly with oleic, palmitic, lauric, and stearic acid. Moreover, β-cryptoxanthin linoleate, linolenate, and stearate were detected for the first time in Harogem cultivar. Variation in carotenoid content and composition was observed, with the highest carotenoid content being recorded in Tudor, Harogem, and Mamaia cultivars. The predominant fatty acids determined by gas chromatography-mass spectrometry (GC-MS) were linoleic (up to 47%), palmitic (up to 32.7%), and linolenic (up to 17.16%), with small variations among cultivars. In-tube extraction technique (ITEX)/GC-MS was applied for profiling the volatiles in apricot fruits and 120 compounds were identified, with terpenoids and esters as the most abundant classes. Principal component analysis (PCA) revealed that the carotenoids and the fatty acids profile can be used for variety authentication and discrimination in apricots.